TOKSISITAS AIR TERCEMAR INDUSTRI PENYAMAKAN KULIT DAERAH SUKAREGANG, GARUT, JAWA BARAT TERHADAP AKAR TANAMAN BAWANG MERAH (ALLIUM CEPA L.) - Fitri, Elisa
Tannery waste in the Sukaregang area, Garut, West Java has been reported to have contributed to water pollution in the Cigulampeng River and paddy fields in the Sukaregang area. Pollution is thought to occur because of the heavy chrome metal contained in the wastewater. In the environment, chromium, which were most often found in the form of Cr3+ and Cr6+, is capable of providing toxic effects on living things. This study aims to evaluate the cytotoxicity and genotoxicity of water polluted by tannery wastewater using Allium assay. The parameters of the cytotoxicity test include root growth and mitotic index (IM), while the genotoxicity test includes the aberration index (IA), the presence of micronuclei and binuclei. Allium assay is done by rooting shallots in distilled water for 48 hours, then exposed in contaminated water with a concentration of 25%, 50%, 75%, and 100% for 24 hours. Negative control consists of (K-1) distilled water and (K-2) uncontaminated water. Observation of cytotoxicity and genotoxicity was carried out after making swab preparations with Carnoy fixatives and acetocarmine dyes. Observations showed that contaminated water decreased root growth, although not significantly when compared to the two controls. Contaminated water decreased the mitosis index, with the biggest decrease found in the treatment of 100% ie between 19.78 - 28.23% compared with the two negative controls. Statistically, root length and mitotic index of 100% treatment were most significantly different from K1 (distilled water). Chromosome aberration also increases with increasing concentrations of contaminated water. The highest IA was found in the treatment of 100% contaminated water, namely 19.89%. The highest micronuclei frequency was also found in the 100% treatment, namely 1.91%. Binuklei was found in all concentrations of polluted water with the highest frequency found at 25% treatment, namely 17.31%. Although C.25% produces the highest binuklei, it was not toxic to the roots of onions. The conclusion that can be drawn is that the polluted water of the leather tanning industry in the Sukaregang area of 100% concentration has a toxic effect on the roots of onion.